Prevención de Caídas: Estilos de Vida y Riesgo de Caídas - Jennifer Hillan (EDIS)
Revised! FCS2230-Span, a 1-page fact sheet by Jennifer Hillan, is the Spanish Language version of "Fall Prevention: Lifestyle Factors and Fall Risk." It describes things that may cause people to fall and some easy changes they can make to decrease their risk of falling. Published as part of the Elder Nutrition and Food Safety (ENAFS) program by the UF Department of Family Youth and Community Sciences, October 2004. Revised May 2006.